2014 7th ESA Workshop on Satellite Navigation Technologies and European Workshop on GNSS Signals and Signal Processing (NAVITEC 2014
DOI: 10.1109/navitec.2014.7045151
|View full text |Cite
|
Sign up to set email alerts
|

Use of weak GNSS signals in a mission to the moon

Abstract: According to the European Space Agency (ESA) Lunar Exploration program, the use of GNSS weak-signal navigation in future lunar exploration missions has the potential to increase the robustness of the navigation during all mission phases and improve considerably its autonomy. The major objectives of the ESA Moon-GNSS project have been to determine the feasibility of using GNSS (GPS/Galileo) weak-signal technology in future lunar missions to improve the navigation performance in terms of accuracy, cost reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 2 publications
0
16
0
Order By: Relevance
“…These receivers are picking up the spillover of the main lobe of the GNSS transmit antenna pattern around the Earth mask and also signals from the weaker side lobes of the antenna pattern. Research presented in [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ] shows feasibility studies of GNSS as navigation system for space missions in High Earth Orbits (HEO) and beyond up to Moon altitude. Other research work, such as [ 9 , 10 , 11 , 12 ] and [ 13 ] has proposed GNSS receivers designed for such missions and the demonstration of a receiver positioning in HEO is detailed in [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…These receivers are picking up the spillover of the main lobe of the GNSS transmit antenna pattern around the Earth mask and also signals from the weaker side lobes of the antenna pattern. Research presented in [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ] shows feasibility studies of GNSS as navigation system for space missions in High Earth Orbits (HEO) and beyond up to Moon altitude. Other research work, such as [ 9 , 10 , 11 , 12 ] and [ 13 ] has proposed GNSS receivers designed for such missions and the demonstration of a receiver positioning in HEO is detailed in [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Promising experimental results presented in Powell et al (1999) and Balbach et al (1998) have demonstrated that by modifying the traditional signal processing techniques, GNSS can also be used in higher orbits such as medium Earth orbit (MEO) and high Earth orbit (HEO). More recent research studies have shown the interest of the scientific space community to investigate the potential use of GNSS as navigation system for lunar missions (Manzano-Jurado et al, 2014;Silva et al, 2013;Capuano et al, 2014aCapuano et al, , 2014bPalmerini et al, 2009). Being its service originally conceived for Earth applications, the GNSS transmitters point towards the Earth, making their transmitted signals very weak above the GNSS constellation.…”
Section: Introductionmentioning
confidence: 99%
“…Being its service originally conceived for Earth applications, the GNSS transmitters point towards the Earth, making their transmitted signals very weak above the GNSS constellation. However, some of these first studies (see e.g., Manzano-Jurado et al, 2014;Capuano et al, 2014a;Silva et al, 2013) have revealed that although weak, GNSS signals from the side lobes of the GNSS transmitters antennas or from the spillover of the main lobe can still be acquired and tracked successfully. Experimental demonstrations have been presented in Balbach et al (1998) for HEO, while theoretical studies have been described in Capuano et al (2014a) for higher orbits up to moon altitude.…”
Section: Introductionmentioning
confidence: 99%
“…For deep space transfer orbits and deep space target orbits, the GPS is not good enough. Several researchers investigated weak GNSS signal navigation for the deep space probes [6][7][8]. Witternigg et al introduced how GPS and Galileo could be used for orbit determination in future missions to the Moon [8].…”
Section: Introductionmentioning
confidence: 99%
“…The methods introduced in [1][2][3][4][5] can be considered as absolute navigation (or absolute autonomous orbit determination) because the estimated orbit refers to an inertial or quasi-inertial frame. Methods introduced in [6][7][8][9][10][11][12][13][14] can be classified as relative navigation. Relative navigation seeks optimal estimates for the position and velocity of one satellite relative to the other one.…”
Section: Introductionmentioning
confidence: 99%